Hybrid hydrogel based on porcine-derived matrix with gallic acid and cerium-doped mesoporous bioactive glass for diabetic wound healing - Hao Zeng; Qinghong Lai; Wuqiang Liao; Jiajin Tu; Junfeng Sun (Materials & Design)
Macrophage aggregation and excessive inflammation are prevalent issues in diabetic wounds, often resulting in impaired wound healing. Consequently, hydrogel dressings with immunomodulatory properties hold significant potential for clinical application in the management of diabetic wound healing. Nonetheless, existing immunomodulatory hydrogels typically necessitate intricate interventions and costly treatments. The researchers developed a novel gallic acid (GA) hybrid hydrogel with built-in immunomodulatory capabilities to speed up the healing of diabetic wounds. This hybrid hydrogel matrix was synthesized using a porcine acellular dermal matrix (Padm) and incorporated novel bioactive glass nanoparticles (MBG) doped with cerium (Ce) and GA. The integration of these components preserved the natural structure of the Padm while imparting it with immunomodulatory capabilities. In vitro experiments demonstrated the favorable biocompatibility and robust immunomodulatory capabilities of the GA-Padm@Ce hybrid hydrogel. The immunomodulatory properties suggest that the GA-Padm@Ce hybrid hydrogel can be utilized for safe and effective treatment, facilitating the acceleration of the three stages of wound healing. Thus, it is expected to become an optimal dressing for diabetic wound treatment.